HIV/STD prevalence and test uptake among african in Guangzhou, China: an analysis of data from hospital-based surveillance - Xiong, Mingzhou; Yang, Menglan; Zhao, Peizhen; Huang, Shujie; Wang, Cheng (BMC infectious diseases, 2023)
Human immunodeficiency virus (HIV) and sexually transmitted diseases (STDs) cause substantial morbidity and mortality both in African and China. However, there is limited data available on the prevalence of HIV/STDs and the uptake of testing experience ever during in China among African migrants. A venue-based survey was conducted at a tertiary hospital in Guangzhou to investigate the prevalence of HIV/STDs through laboratory testing and identify the associated factors. A total of 200 eligible participants completed the survey and bring into the analysis from April to October 2019, and the temporary visitors were excluded. The prevalence rates of HIV, syphilis, NG, CT, and HBsAg among the participants were 1.0%, 2.5%, 1.0%, 1.5%, and 5.5%, respectively. The overall reported rate of HIV/STD testing was 37.0%, with rates of 23.0% for HIV, 16.5% for syphilis, 12.5% for NG, 6.5% for genital herpes, 5.0% for condyloma acuminata, and 2.5% for CT. HIV/STD testing was associated with living environment in Guangzhou, having medical insurance in China, and utilizing health services in China in the past year. HIV/STDs are prevalent among Africans in Guangzhou, and the epidemic is likely to spread due to a significant proportion of unprotected sexual behaviors and low rates of HIV/STD testing. Urgent interventions, including targeted health education, promotion of health service utilization, and active surveillance of HIV/STDs, are needed to reduce the risk of HIV/STD transmission.